2023
DOI: 10.3171/2022.11.spine22719
|View full text |Cite
|
Sign up to set email alerts
|

A novel scoring system concept for de novo spinal infection treatment, the Spinal Infection Treatment Evaluation Score (SITE Score): a proof-of-concept study

Abstract: OBJECTIVE De novo infections of the spine are an increasing healthcare problem. The decision for nonsurgical or surgical treatment is often made case by case on the basis of physician experience, specialty, or practice affiliation rather than evidence-based medicine. To create a more systematic foundation for surgical assessments of de novo spinal infections, the authors applied a formal validation process toward developing a spinal infection scoring system using principles gained from other spine severity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…To the best of our knowledge, no guidelines exist for surgery versus conservative treatment relative to patients with spondylodiscitis, nor is there a threshold standard for operative intervention [3][4][5]. Our results show an acceptable accuracy performance for the SITE score in patients with spondylodiscitis.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…To the best of our knowledge, no guidelines exist for surgery versus conservative treatment relative to patients with spondylodiscitis, nor is there a threshold standard for operative intervention [3][4][5]. Our results show an acceptable accuracy performance for the SITE score in patients with spondylodiscitis.…”
Section: Discussionmentioning
confidence: 63%
“…The discrimination between surgery and conservative treatment appeared to be effective for the SITE score when compared with the other scores. Pluemer et al [ 4 ] reported a cutoff value of ≤8 (sensitivity, 100.0%; specificity, 95.7%). This observation is in accordance with our study results that the optimal cutoff value was ≤8.5 (sensitivity, 80.6%; specificity, 81.2%) when the panel decided in favor of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations